2003
DOI: 10.1081/jcmr-120022263
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Myocardial Flow Reserve on the Detection of Coronary Artery Disease by Perfusion Imaging Methods: An NHLBI WISE Study

Abstract: Myocardial flow reserve (MFR) is not routinely assessed in myocardial perfusion imaging (MPI) studies but has been hypothesized to affect test accuracy when assessing disease severity by coronary vessel lumenography. Magnetic resonance imaging (MRI) is an emerging diagnostic technique that can both perform MPI and assess MFR. We studied women (n = 184) enrolled in the Women's Ischemia Syndrome Evaluation (WISE) study with symptoms suggesting ischemic heart disease. Tests performed were coronary angiography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(46 citation statements)
references
References 34 publications
1
44
1
Order By: Relevance
“…In another study, CMR myocardial perfusion reserve was found to be comparable to standard gated SPECT techniques. 142 Most recently, in a series of 1000 examinations (including 257 women) for high-dose dobutamine stress, CMR was found to have a safety profile comparable to that of high-dose dobutamine echocardiography. 144 Previous data in 208 patients (including 61 women) suggested greater accuracy of high-dose dobutamine CMR as compared with high-dose dobutamine echocardiography with quantitative coronary angiography as the reference standard, 145 which supports its use as a measure of inducible myocardial ischemia.…”
Section: Diagnosismentioning
confidence: 99%
“…In another study, CMR myocardial perfusion reserve was found to be comparable to standard gated SPECT techniques. 142 Most recently, in a series of 1000 examinations (including 257 women) for high-dose dobutamine stress, CMR was found to have a safety profile comparable to that of high-dose dobutamine echocardiography. 144 Previous data in 208 patients (including 61 women) suggested greater accuracy of high-dose dobutamine CMR as compared with high-dose dobutamine echocardiography with quantitative coronary angiography as the reference standard, 145 which supports its use as a measure of inducible myocardial ischemia.…”
Section: Diagnosismentioning
confidence: 99%
“…Few studies have assessed the utility of CMR stress testing specifically in women [15,25-27]. The prior reports vary in imaging technology (older pulse sequences and different coil technology) [25], pre-test probability (patients with known CAD and prior MI included) [26], and CAD prevalence (low-risk ED patients with chest pain) [27]. The sensitivities and specificities in the previous studies ranged from 57%-95% and 75%-100%, which concurs with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Regions of myocardial perfusion deficit were determined by a consensus of experience MRI readers who then provided the qualitative reading, MRI QL . A semi-quantitative reading (MRI SQ ) of the MPI defect was performed using the product of the normalized uptake slope and signal gain from baseline to peak (5). Additionally, the myocardial flow reserve (MFR) was calculated as the ratio of the normalized stress to rest uptake slope.…”
Section: Cardiovascular Magnetic Resonancementioning
confidence: 99%
“…Multiple factors such as MFR and processing noise are known to affect the reproducibility, diagnostic and prognostic accuracy of MPI assessed by MRI (5,(11)(12)(13). Further, assessing MPI success using the degree of agreement with the cath lab-determined coronary artery stenosis level is not straight forward due to MRI's sensitivity to microvascular disease, collateral circulation and myocardial flow reserve (14).…”
Section: Diagnostic Versus Prognosticmentioning
confidence: 99%